Surface treatment method for improving corrosion resistance of copper-chromium-zirconium alloy, alloy obtained through surface treatment method and application of alloy
The supersaturated solid solution is formed through surface sandblasting and laser quenching treatment, which solves the problem of stress corrosion and cracking of copper-chromium zirconium alloy in the natural environment, and significantly improves its corrosion resistance.
Patent Information
- Application Number
- CN202411714016.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
High-strength, high-conducting copper-chromium zirconium alloys have the risk of stress corrosion cracking in natural environments, especially in ammonium ion-containing environments, and the prior art has failed to effectively reduce its stress sensitivity and improve its corrosion resistance.
After surface sandblasting treatment, an oxide film is formed in the oven, and then laser scanning and quenching treatment is used to form a supersaturated solid solution to the surface layer of the copper-chromium zirconium alloy, reducing the film tensile stress and stress corrosion sensitivity.
It significantly reduces the stress corrosion sensitivity of copper-chromium zirconium alloy, improves its corrosion resistance, and reduces the risk of stress corrosion cracking of the casing clamps.
Smart Images

Figure CN119530686A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alloy surface treatment, specifically a surface treatment technology for high-strength copper alloy for power grid, especially a surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy and the obtained alloy and application. Background Art
[0002] Substations are key nodes in high-voltage power transmission and transformation systems. The down conductor system in substations is an important power facility that connects transmission lines and substation equipment. Its structural safety directly affects the normal and stable operation of substations and even lines. The down conductor system consists of down conductors, hardware for connecting down conductors to busbars, and hardware for connecting down conductors to main equipment terminals. Once the terminal is plastically deformed or even damaged, the seal of the main transformer bushing will fail, leading to the serious consequences of transformer shutdown and power outage of the entire station line. The terminal not only bears mechanical loads and wind loads, but also needs to ensure excellent electrical contact to achieve large current flow. Therefore, the material used as the terminal is required to have good electrical conductivity, excellent mechanical strength and good environmental tolerance.
[0003] As a typical form of terminal block, the bushing clamp is currently mainly made of H62 brass or T2 copper. The cracking phenomenon of brass bushing terminals in brass bushing clamps is mainly due to the stress corrosion sensitivity of brass. Under the combined action of bolt preload and the surrounding corrosive environment, cracks are formed and rapidly expand, resulting in brittle fracture without warning. Bushing clamps made of copper have also experienced multiple heating defects that cause failures. The copper clamp has plastic deformation defects under the combined action of load and wind load, resulting in a large gap between the clamp and the terminal copper head. The reduction in effective contact area leads to an increase in local contact resistance and overheating. Local temperature rise and overheating lead to a decrease in the softening strength of the clamp and further plastic deformation. At the same time, the traditional brass casting process consumes a lot of energy and causes serious pollution. The electrical conductivity of brass itself is lower than that of pure copper, and there is heat loss during operation. With the development of transformers towards ultra-high voltage and ultra-large capacity, higher and higher requirements are placed on the strength and conductivity of bushing clamp materials.
[0004] Copper-chromium-zirconium alloy is a typical high-strength and high-conductivity copper alloy. In recent years, it has been widely used in integrated circuit lead frames, terminal blocks, new energy charging piles, high-speed railway contact networks and other fields.
[0005] Chinese patent document [201310216235.X] discloses a process for preparing a high-strength and high-conductivity copper-chromium-zirconium alloy long conductor. The copper-chromium-zirconium alloy rod (wire) is flash-butt-welded and then subjected to continuous extrusion treatment to refine the weld and matrix grains, followed by cold deformation and aging treatment. This process can simultaneously improve the mechanical properties of the copper-chromium-zirconium alloy matrix and weld, and make the mechanical and electrical properties of the weld close to the matrix, solving the problem of reduced performance of the copper-chromium-zirconium alloy after welding, and thus preparing a copper-chromium-zirconium alloy long conductor with excellent performance. The conditions applicable to this invention are high-strength and high-conductivity copper-chromium-zirconium alloy, and the diameter range of the copper-chromium-zirconium alloy rod (wire) used for connection is 10-40mm.
[0006] Chinese patent document [202111019527.5] discloses a method for preparing a highly softening-resistant copper-chromium-zirconium alloy rod, comprising: S1, weighing Cr, Zr and Cu respectively; S2, charging Cr, Zr and Cu into a crucible for vacuum induction melting to obtain a copper-chromium-zirconium alloy solution; S3, casting the copper-chromium-zirconium alloy solution by an upward continuous casting method to obtain an alloy ingot; S4, heating the alloy ingot to, and performing heat preservation treatment, and then performing upsetting and drawing forging, and after the forging is completed, performing outer circle treatment on the ingot to obtain an alloy rod; then performing solid solution heat treatment on the alloy rod; S5, performing a primary cold working, a primary aging treatment, a secondary cold working and a secondary aging treatment on the alloy rod after the solid solution heat treatment to obtain the desired copper-chromium-zirconium alloy rod; the copper-chromium-zirconium alloy rod prepared by this method has high electrical conductivity and metal strength, and its high temperature softening resistance is significantly improved compared with that of general copper-chromium-zirconium alloy rods, and is suitable for large-scale promotion.
[0007] Chinese patent document [201510986599.5] discloses a copper-chromium-zirconium alloy, which is made of the following raw materials by weight: 0.7-2.0% chromium, 0.05-0.3% zirconium, 0.01-0.08% magnesium, 0.01-0.1% yttrium, and the balance is copper. Its preparation method comprises the following steps in sequence: (1) copper, chromium, zirconium, magnesium, and yttrium are prepared in proportion, and vacuum purified smelting and split-flow casting are performed to obtain a casting blank; (2) the casting blank is homogenized and hot extruded to obtain a rod blank; (3) the rod blank is subjected to solid solution treatment; (4) the solution treated rod blank is subjected to cold deformation processing; (5) the material obtained after cold deformation processing is subjected to aging treatment to obtain the desired chromium-zirconium-copper alloy. The copper-chromium-zirconium alloy prepared by the invention has good comprehensive properties, with room temperature tensile strength greater than 520MPa, room temperature elongation greater than 22%, room temperature electrical conductivity greater than 90% IACS, and 350°C high temperature tensile strength greater than 390MPa.
[0008] Chinese patent document [202111679459.5] discloses an electron beam welding process and post-weld heat treatment method for copper-chromium-zirconium alloy. First, the two CuCrZr alloy plates to be welded are surface treated, and then the CuCrZr alloy to be welded is clamped by tooling to prevent deformation during the welding process; the alloy plates to be welded are first preheated by scanning with low power, and then welded at a constant speed and power. After the welding process is completed, the welded parts are first furnace-cooled, and the welding samples are taken out after cooling for half an hour. After standing in the air to room temperature, the above welding operation is repeated once, and after aging heat treatment, a good double-sided welding joint can be obtained, and the obtained joint has a high penetration depth / melt width ratio. This method is suitable for the welding of high-precision accessories. The joint obtained by electron beam welding has a good structure and good tensile performance, which can reach 300MPa. The welded joint after aging treatment can reach more than 350MPa, which can meet the requirements of actual engineering.
[0009] Chinese patent document [202211147747.0] discloses a rapid preparation method for parts with nano-scale chromium phase and high conductivity copper-chromium-zirconium, comprising the following steps: S1, raw material selection: select CuCrZr wire as the base material for arc printing, the diameter of the CuCrZr wire is 1.1-1.2mm, the mass composition of Cr in the CuCrZr wire is 0.5-3wt%, the mass composition of Zr is 0.1-0.8wt%, and the remainder is Cu; S2, arc printing preparation; S3, arc printing; S4, post-processing. The invention combines copper-chromium-zirconium wire with arc printing technology, optimizes and adjusts the parameters of arc printing, and selects CuCrZr wire with appropriate composition, and finally obtains a rapid preparation method for parts with nano-scale chromium phase and high conductivity copper-chromium-zirconium based on plasma welding arc printing, which is the first application of arc printing technology in the field of copper and copper alloys, and has guiding significance for the future development of arc printing technology in the field of copper and copper alloys.
[0010] In general, there are many methods for preparing copper-chromium-zirconium alloys that can achieve high strength and high conductivity. However, when high-strength and high-conductivity copper-chromium-zirconium is used as a terminal for a bushing clamp, it is still at risk of stress corrosion cracking when exposed to the natural environment, especially when exposed to tensile stress containing ammonium ions.
[0011] There is currently no relevant treatment method to reduce the stress sensitivity of copper, chromium and zirconium and improve the corrosion resistance. Summary of the invention
[0012] The technical problem to be solved by the present invention is to overcome the defects of the above-mentioned prior art and provide a copper-chromium-zirconium alloy that can effectively reduce the stress sensitivity of serving in an ammonium ion environment and a surface treatment method for improving the corrosion resistance of the copper-chromium-zirconium alloy, so as to improve the corrosion resistance of the copper-chromium-zirconium alloy and meet the use requirements of the copper-chromium-zirconium alloy in electrical engineering fields such as casing clamps.
[0013] To this end, the present invention adopts the following technical solution.
[0014] In a first aspect, the present invention provides a surface treatment method for improving the corrosion resistance of a copper-chromium-zirconium alloy, comprising:
[0015] The high-strength and high-conductivity copper-chromium-zirconium alloy is subjected to surface sandblasting treatment, and then placed in an oven, kept at 200-250°C for 5-10 minutes, and then taken out for air cooling to form an oxide film on the surface of the copper-chromium-zirconium alloy to reduce the reflectivity of the copper-chromium-zirconium alloy to the laser;
[0016] The copper-chromium-zirconium alloy with an oxide film on its surface is clamped on a workbench, and the surface of the copper-chromium-zirconium alloy is quickly scanned by changing the laser scanning trajectory with a galvanometer combined with the auxiliary movement of the workbench to achieve surface quenching treatment of the copper-chromium-zirconium alloy, and the chromium-zirconium precipitated phase on the surface of the copper-chromium-zirconium alloy is re-melted, so that the Cr and Zr elements are retained in the copper lattice in the form of solid solution atoms to form a supersaturated solid solution.
[0017] The principle of the present invention to improve the corrosion resistance of copper-chromium-zirconium samples is that copper-chromium-zirconium alloy has a relatively obvious stress corrosion cracking phenomenon in an ammonium ion environment. The essential reason is that a copper oxide layer is formed in an ammonium ion environment, and copper ions migrate outward and oxygen ions diffuse inward, which makes the oxide layer thicker. Since copper ions migrate outward to form vacancies in the surface copper lattice, the surface layer containing vacancies tends to shrink, while the remaining part hinders its shrinkage, thereby generating film-induced tensile stress in the surface layer. Film-induced tensile stress significantly increases the stress corrosion sensitivity of the material, resulting in a significant increase in the risk of fracture of the material under external tensile stress. The core idea of the present invention is to use the intrinsic tensile stress of the supersaturated solid solution to resist the vacancy effect formed by the diffusion and dissolution of copper, thereby significantly reducing the stress corrosion sensitivity coefficient of the copper-chromium-zirconium alloy and reducing the stress corrosion cracking risk of the casing clamp made of the copper-chromium-zirconium alloy. The copper-chromium-zirconium alloy used under normal conditions is in an aging state. At this time, the alloy has high strength and high conductivity characteristics, and at this time, chromium and zirconium are second-phase particles embedded in the copper matrix. The present invention utilizes the extremely high energy density of the laser to partially melt the sample surface so that the chromium-zirconium particles are re-melted and dissolved into the copper. The excellent thermal conductivity of the copper material and the rapid scanning of the laser beam are utilized to create the effects of transient heating and transient cooling, so that the surface chromium-zirconium elements exist in the copper lattice in the form of atoms to form a supersaturated solid solution. Since the supersaturated solid solution has intrinsic tensile stress, when copper migrates to form vacancies, most of the shrinkage trend can be offset, thereby reducing the film-induced tensile stress, thereby reducing the stress corrosion sensitivity coefficient and improving the corrosion resistance of the sample. Of course, since the copper alloy has a high reflectivity to the laser and is easy to burn the laser, the sample must first be pre-oxidized to form an oxide film layer to reduce the reflectivity to the laser; and the laser beam cannot be incident vertically on the sample surface, but has an inclination angle of 5-10° to prevent the directly reflected laser from burning the laser.
[0018] Furthermore, the laser is a commercial fiber-coupled semiconductor red laser source, the light source power is 100-500W, the scanning rate is 300-1200mm / s, and the incident angle of the laser beam relative to the copper-chromium-zirconium alloy surface is 80-85°.
[0019] Furthermore, the laser forms a square spot with a side length of 1-2 mm, and the light emission mode of the laser is a continuous laser mode.
[0020] Furthermore, the high-strength and high-conductivity copper-chromium-zirconium alloy is obtained by the following method:
[0021] The copper-chromium-zirconium alloy ingot is hot rolled and cold rolled, and then the copper-chromium-zirconium alloy is subjected to a solid solution aging treatment, so that the Cr and Zr elements are dispersed in the copper matrix in the form of second phase particles, and a high-strength and high-conductivity copper-chromium-zirconium alloy is obtained.
[0022] Furthermore, the copper-chromium-zirconium alloy ingot is obtained by the following method:
[0023] With Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper as raw materials, copper-chromium-zirconium alloy ingots were prepared by induction melting furnace according to alloy component ratio.
[0024] Furthermore, the induction melting furnace adopts a melting temperature of 1300-1500°C and a heat preservation casting temperature of 1200-1250°C.
[0025] In a second aspect, the present invention provides a copper-chromium-zirconium alloy obtained by the above-mentioned surface treatment method, with a Cr content of 0.3wt.%-5wt.%, a Zr content of 0.05wt.%-0.3wt.%, and the rest being Cu.
[0026] Furthermore, the internal structure of the copper-chromium-zirconium alloy obtained by surface quenching treatment is an aged CuCrZr structure, a large number of Cr and Zr second phase particles are precipitated and embedded in the Cu grains during the aging process, and the residual Cr and Zr element content in the Cu lattice is less than 0.03wt.%; the surface structure of the copper-chromium-zirconium alloy is a solid solution state, and its thickness is 10-100μm.
[0027] Furthermore, the solid solution surface layer is composed of Cu grains only, and does not contain Cr and Zr second phase particles, and the Cr and Zr elements exist in the Cu lattice in the form of substitution atoms.
[0028] In a third aspect, the present invention also provides an application of the copper-chromium-zirconium alloy, wherein the copper-chromium-zirconium alloy is processed into a casing clamp.
[0029] The copper-chromium-zirconium alloy surface treatment method provided by the present invention has the following beneficial effects:
[0030] (1) The copper-chromium-zirconium alloy film of the present invention has very low stress-induced stress and stress corrosion sensitivity and has excellent resistance to stress corrosion cracking.
[0031] (2) The surface treatment method of the present invention is simple and easy to implement, with a short treatment process, which is conducive to large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 A schematic diagram of film-induced stress and stress corrosion sensitivity of different samples in a specific embodiment of the present invention;
[0034] Figure 2 TEM images of different regions of the cross section of the sample of Example 1 of the present invention, wherein (a) is the surface structure treated by laser, in which no second phase particles are observed; and (b) is the internal structure of the sample, in which a large number of second phase particles are observed embedded in the copper matrix. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments.
[0036] The present invention provides a surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy, the steps of which are as follows:
[0037] In the first step, Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper are used as raw materials, and according to the alloy component ratio, a copper-chromium-zirconium alloy ingot is prepared by an induction melting furnace, the melting temperature is 1300-1500°C, and the insulation casting temperature is 1200-1250°C.
[0038] In the second step, the obtained copper-chromium-zirconium alloy ingot is hot-rolled and cold-rolled, and then the copper-chromium-zirconium alloy is subjected to solid solution aging treatment to disperse Cr and Zr elements in the copper matrix in the form of second phase particles, thereby obtaining a copper-chromium-zirconium alloy with high strength and high conductivity. The hot rolling temperature is not less than 900°C, the cumulative cold rolling reduction is not less than 70%, the solid solution temperature is 950-1000°C, the holding time is 30-60min, and the copper-chromium-zirconium alloy is quenched and cooled.
[0039] The third step is to machine the copper-chromium-zirconium alloy into a casing wire clamp product, put it into a common oven after surface sandblasting, keep it at 200-250℃ for 5-10 minutes, take it out and air cool it, so that a 3-5μm thick oxide film is formed on the surface of the casing wire clamp product.
[0040] The fourth step is to clamp the above-mentioned casing clamp product on the workbench, use a galvanometer to change the laser scanning trajectory and combine the workbench auxiliary movement to quickly scan the product surface to achieve surface quenching treatment. The laser used is a commercial fiber-coupled semiconductor red laser source, the light source power is 100-500W, the spot is a square spot with a side length of 1-2mm, the light output mode is a continuous laser mode, the scanning rate is 300-1200mm / s, and the laser beam incident angle relative to the product surface is 80-85°.
[0041] The copper-chromium-zirconium alloy obtained by the above surface treatment method has a composition of 0.3wt.%-5wt.% Cr, 0.05wt.%-0.3wt.% Zr, and the rest is Cu; the internal structure of the alloy is a solid solution-aged CuCrZr structure, a large number of Cr and Zr second phase particles are precipitated and embedded in Cu grains during the aging process, and the content of Cr and Zr elements remaining in the Cu lattice is less than 0.03wt.%; the surface structure of the alloy is a solid solution state, the thickness of the solid solution surface layer structure is 10-100μm, the surface layer is only composed of Cu grains, does not contain Cr and Zr second phase particles, and Cr and Zr elements exist in the Cu lattice in the form of replacement atoms.
[0042] Example 1
[0043] This embodiment is a surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy, and the steps are as follows:
[0044] (1) Using Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper as raw materials, according to the alloy composition ratio of Cu0.3wt.%Cr0.05wt.%Zr, a copper-chromium-zirconium alloy ingot was prepared by an induction melting furnace, the melting temperature was 1300°C, and the insulation casting temperature was 1200°C.
[0045] (2) The Cu0.3wt.%Cr0.05wt.%Zr ingot is hot rolled and cold rolled, and then the copper-chromium-zirconium alloy is subjected to solid solution aging treatment, so that the Cr and Zr elements are dispersed in the copper matrix in the form of second phase particles, and a copper-chromium-zirconium alloy with high strength and high conductivity is obtained. The hot rolling temperature is 900℃, the cold rolling cumulative reduction is 70%, the solid solution temperature is 950℃, the holding time is 30min, and the quenching is cooled.
[0046] (3) The Cu0.3wt.%Cr0.05wt.%Zr alloy is machined into a casing wire clamp product. After the surface is sandblasted, it is placed in a common oven and kept at 200°C for 5 minutes. It is taken out and air-cooled to form a 3μm thick oxide film on the surface of the casing wire clamp product.
[0047] (4) The above-mentioned casing clamp product is clamped on a workbench, and a galvanometer is used to change the laser scanning trajectory and the workbench is used to assist in the movement to quickly scan the surface of the casing clamp product to achieve surface quenching treatment. The laser used is a commercial fiber-coupled semiconductor red laser source with a light source power of 500W, a square spot with a side length of 2mm, a continuous laser mode, a scanning rate of 1200mm / s, and an incident angle of 80° relative to the sample surface.
[0048] Example 2
[0049] This embodiment is a surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy, and the steps are as follows:
[0050] (1) Using Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper as raw materials, according to the alloy composition ratio of Cu5wt.%Cr3wt.%Zr, a copper-chromium-zirconium alloy ingot was prepared by an induction melting furnace, the melting temperature was 1500°C, and the insulation casting temperature was 1250°C.
[0051] (2) The Cu5wt.%Cr3wt.%Zr ingot is hot rolled and cold rolled, and then the copper-chromium-zirconium alloy is subjected to solid solution aging treatment to disperse the Cr and Zr elements in the copper matrix in the form of second phase particles, thereby obtaining the basic properties of high strength and high conductivity. The hot rolling temperature is 950℃, the cold rolling cumulative reduction is 80%, the solid solution temperature is 100℃, the holding time is 60min, and the alloy is quenched in water.
[0052] (3) The Cu5wt.%Cr3wt.%Zr alloy is machined into a casing wire clamp product. After the surface is sandblasted, it is placed in a common oven and kept at 250°C for 10 minutes. It is taken out and air-cooled to form a 5μm thick oxide film on the surface of the product.
[0053] (4) The above product is clamped on a workbench, and a galvanometer is used to change the laser scanning trajectory and the workbench is used to assist in the movement to quickly scan the product surface to achieve surface quenching treatment. The laser used is a commercial fiber-coupled semiconductor red laser source, the light source power is 100W, the spot is a square spot with a side length of 1mm, the light output mode is a continuous laser mode, the scanning rate is 300mm / s, and the laser beam incident angle relative to the sample surface is 85°.
[0054] Comparative Example 1
[0055] (1) Using Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper as raw materials, according to the alloy composition ratio of Cu0.3wt.%Cr0.05wt.%Zr, a copper-chromium-zirconium alloy ingot was prepared by an induction melting furnace, the melting temperature was 1300°C, and the insulation casting temperature was 1200°C.
[0056] (2) The Cu0.3wt.%Cr0.05wt.%Zr ingot is hot rolled and cold rolled, and then the copper-chromium-zirconium alloy is subjected to solid solution aging treatment, so that the Cr and Zr elements are dispersed in the copper matrix in the form of second phase particles, and the basic properties of high strength and high conductivity are obtained. The hot rolling temperature is 900℃, the cold rolling cumulative reduction is 70%, the solid solution temperature is 950℃, the holding time is 30min, and the quenching is cooled.
[0057] (3) The Cu0.3wt.%Cr0.05wt.%Zr alloy is machined into a casing clamp product.
[0058] Comparative Example 2
[0059] Steps (1), (2) and (3) are the same as those in Example 1. The incident angle used in step (4) is 90°, and the other parameters are the same as those in Example 1.
[0060] After 10 seconds of scanning, the laser alarmed and the operation was interrupted. The reason was that the laser energy reflected back to the laser exceeded the limit and burned some laser components.
[0061] Comparative Example 3
[0062] Steps (1), (2) and (4) are the same as those in Example 1. The oven temperature used in step (3) is room temperature, and the remaining parameters are the same as those in Example 1.
[0063] After scanning for 5 seconds, the laser alarmed and the work was interrupted. The reason was that the laser energy reflected back to the laser exceeded the limit and burned some laser components.
[0064] The casing clamp sample (1#) obtained in comparative example 1, the casing clamp sample (2#) obtained in example 1 and the casing clamp sample (3#) obtained in example 2 were subjected to slow tensile test under the same experimental conditions. The film-induced stress and stress corrosion sensitivity were obtained through the tensile curve. The test tensile rate was 1×10 -6 s -1 The samples were immersed in a 0.02M ammonium chloride solution. The results are shown in the attached Figure 1 It can be seen that the film-induced stress of the untreated casing clamp sample is as high as 105MPa, and the stress corrosion sensitivity is 25%; after the surface treatment by the method of the present invention, the film-induced stress and sensitivity are greatly reduced.
[0065] The casing clamp sample of Example 1 was sampled from the surface to the center to prepare transmission electron microscope samples for observation. Figure 2 The results show that the surface structure is a single-phase solid solution, without second-phase particles, reflecting the typical characteristics of the solution-treated state; the internal structure is a typical aging state structure, with second-phase nanoparticles dispersed on the copper matrix.
[0066] As shown in Comparative Examples 2 and 3, when the treatment process of the present invention is not implemented, equipment damage may occur.
[0067] The above specific implementation methods are used to illustrate the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications and changes made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.
Claims
1. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy, characterized in that: include: The high-strength and high-conductivity copper-chromium-zirconium alloy is subjected to surface sandblasting treatment, and then placed in an oven, kept at 200-250°C for 5-10 minutes, and taken out for air cooling to form an oxide film on the surface of the copper-chromium-zirconium alloy to reduce the reflectivity of the copper-chromium-zirconium alloy to the laser; The copper-chromium-zirconium alloy with an oxide film on its surface is clamped on a workbench, and the surface of the copper-chromium-zirconium alloy is quickly scanned by changing the laser scanning trajectory with a galvanometer combined with the auxiliary movement of the workbench to achieve surface quenching treatment of the copper-chromium-zirconium alloy, and the chromium-zirconium precipitated phase on the surface of the copper-chromium-zirconium alloy is re-melted, so that the Cr and Zr elements are retained in the copper lattice in the form of solid solution atoms to form a supersaturated solid solution.
2. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy according to claim 1, characterized in that: The laser is a commercial fiber-coupled semiconductor red laser source, the light source power is 100-500W, the scanning rate is 300-1200mm / s, and the incident angle of the laser beam relative to the copper-chromium-zirconium alloy surface is 80-85°.
3. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy according to claim 2, characterized in that: The laser forms a square light spot with a side length of 1-2 mm, and the light emission mode of the laser is a continuous laser mode.
4. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy according to any one of claims 1 to 3, characterized in that: The high-strength and high-conductivity copper-chromium-zirconium alloy is obtained by the following method: The copper-chromium-zirconium alloy ingot is hot rolled and cold rolled, and then the copper-chromium-zirconium alloy is subjected to solid solution aging treatment, so that the Cr and Zr elements are dispersed in the copper matrix in the form of second phase particles, and a copper-chromium-zirconium alloy with high strength and high conductivity is obtained.
5. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy according to claim 4, characterized in that: The copper-chromium-zirconium alloy ingot is obtained by the following method: With Cu10wt.%Cr master alloy, Cu5wt.%Zr master alloy and cathode electrolytic copper as raw materials, copper-chromium-zirconium alloy ingots were prepared by induction melting furnace according to alloy component ratio.
6. A surface treatment method for improving the corrosion resistance of copper-chromium-zirconium alloy according to claim 5, characterized in that: The induction melting furnace adopts a melting temperature of 1300-1500°C and a heat preservation casting temperature of 1200-1250°C.
7. A copper-chromium-zirconium alloy obtained by the surface treatment method according to any one of claims 1 to 6, characterized in that: In the copper-chromium-zirconium alloy obtained by surface quenching treatment, the Cr content is 0.3wt.%-5wt.%, the Zr content is 0.05wt.%-0.3wt.%, and the rest is Cu.
8. The copper-chromium-zirconium alloy according to claim 7, characterized in that: The copper-chromium-zirconium alloy obtained by surface quenching treatment has an internal structure of an aged CuCrZr structure, a large number of Cr and Zr second phase particles are precipitated and embedded in Cu grains during the aging process, and the residual Cr and Zr element content in the Cu lattice is less than 0.03wt.%; the surface structure of the copper-chromium-zirconium alloy is a solid solution state, and its thickness is 10-100μm.
9. The copper-chromium-zirconium alloy according to claim 8, characterized in that: The solid solution surface layer is composed of Cu grains only, and does not contain Cr and Zr second phase particles. Cr and Zr elements exist in the Cu lattice in the form of replacement atoms.
10. Use of the copper-chromium-zirconium alloy according to any one of claims 7 to 9, characterized in that: Processing copper-chromium-zirconium alloy into casing clamps.
Citation Information
Patent Citations
Production process of high-strength high-conductivity copper-chromium-zirconium alloy long wire
CN103273271A
Copper chromium zirconium alloy and preparing method thereof
CN105543540A
A method for preparing high-resistance copper-chromium-zirconium alloy rods
CN113736970B
Electron beam welding process and postweld heat treatment method for copper-chromium-zirconium alloy
CN114309910A
A rapid preparation method for high-conductivity copper-chromium-zirconium parts with nano-chromium phase
CN115533113B